Long-Term Survival of Canadian Liver Transplant Recipients Remains Stagnant— A Cohort Study on the Evolution of Cause-Specific Mortality - Zhao, Xun; Xu, Chaoqun; Bera, Chinmay; Arisar, Fakhar Ali Qazi; Naghibzadeh, Maryam; Azhie, Amirhossein; Chen, Shiyi; Xu, Wei; Selzner, Nazia; Tsien, Cynthia; Lilly, Leslie; Jaeckel, Elmar; et al. (Digestive diseases and sciences, 2025)
Objective Recent U.S. registry publications showed no improvement in long-term survival post-liver transplant in the last three decades. Cardiovascular disease was a leading cause of post-transplant mortality. This observation urged us to assess the trend in long-term survival of Canadian liver transplant recipients (LTR) in comparison to other countries, and examine trends in cause-specific mortality. Methods Consecutive adult subjects seen at the liver transplant center between September 1984 and December 2020 at the University Health Network (UHN) in Toronto, Canada, were reviewed. The study period was divided into seven 5-year eras. Comparisons between eras were made to assess trend over time. Cause-specific mortality were studied up to 10 years post-transplant. Results In total, 2972 subjects were included. Overall, no significant improvement in long-term survival was observed over the seven eras. No significant difference in the risk of cardiovascular, malignancy, or infection-related mortality was observed across the eras. Significant improvements were observed in graft failure-related mortality. Compared to the age and sex matched general population, LTRs demonstrated a significantly higher mortality and shorter life expectancy. Conclusion Advances in transplant medicine over the last 35 years translated into a decrease in graft-related mortality. However, overall, there was no significant change in long-term survival considering all causes. Despite advances in post-transplant management, it has not led to a decrease in cardiovascular, malignancy or infection-related mortality in transplant recipients. Further research is warranted on the cause of stagnation in these areas and improving long-term post-transplant outcomes. Graphical Abstract Cumulative incidence of cause-specific mortality post-liver transplant for the 7 eras. Top left, cardiovascular-related mortality. Top right graft failure-related mortality. Bottom left, malignancy-related morality. Bottom right, infection-related mortality.